2018
DOI: 10.3389/fphar.2018.00105
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Mechanism of Geniposide: Inhibiting the Hyperpermeability of Fibroblast-Like Synoviocytes via the RhoA/p38MAPK/NF-κB/F-Actin Signal Pathway

Abstract: Geniposide (GE) is the extraction and purification of iridoid glycosides from the Gardenia jasminoides Ellis, which is a promising anti-inflammatory drug, but its mechanism of actions on rheumatoid arthritis (RA) has not been clarified. This study investigated the molecular mechanism behind GE reduced the high permeability of fibroblast-like synoviocytes (FLSs) derived from SD rats with adjuvant arthritis (AA), with the aims of observing the action of GE in AA rats and exploring new therapeutic strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 52 publications
(53 reference statements)
0
32
0
Order By: Relevance
“…The overexpression of these three factors was described in rheumatoid arthritis, which indicates that their inhibition would be a promising new therapeutic target [41][42][43]. Moreover, an analysis that was performed by Deng et al confirmed the important contribution of RhoA in cartilage destruction and the metabolism of synoviocytes [44]. Also, Kumar et al and Cho et al confirmed the role of RhoA in mediating the process of the formation of a network of new blood vessels, as well as with the migration of epithelial cells, which were mediated by the TGFβ and E-cadherin pathway [45,46].…”
Section: Discussionmentioning
confidence: 93%
“…The overexpression of these three factors was described in rheumatoid arthritis, which indicates that their inhibition would be a promising new therapeutic target [41][42][43]. Moreover, an analysis that was performed by Deng et al confirmed the important contribution of RhoA in cartilage destruction and the metabolism of synoviocytes [44]. Also, Kumar et al and Cho et al confirmed the role of RhoA in mediating the process of the formation of a network of new blood vessels, as well as with the migration of epithelial cells, which were mediated by the TGFβ and E-cadherin pathway [45,46].…”
Section: Discussionmentioning
confidence: 93%
“…32 Moreover, geniposide also exerted potential anti-inammatory activity via inhibition of the NF-kB signaling pathway. 33 Hence, the suppressive effects of RIS on inammatory mediators may be, at least in part, due to the presence of these two compounds. Further studies will be conducted to identify other active components responsible for the anti-inammatory effect of RIS.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous researches have shown that betulinic acid, kaempferol, leonurine, oxymatrine, and piperlongumine can inhibit the migration and invasion of FLS in RA models (Li et al, ; Liang et al, ; Liu, Feng, et al, ; Pan et al, ; Sun, Xu, Du, Zhang, & Zhu, ). Triptolide, celastrol, geniposide, paeoniflorin, clematichinenoside AR, glycyrrhetinic acid, kirenol, cucurbitacin E, 1,7‐dihydroxyl‐3,4‐dimethoxylxanthone, calycosin, catechin, cyanidin‐3‐glucoside, quercetin, α‐mangostin, leonurine, norisoboldine, oxymatrine, caffeic acid, paeonol, resveratrol, shikonin, and 3 R ‐(4′‐hydroxyl‐3′‐ O ‐β‐ d ‐glucopyranosyl phenyl)‐dihydro isocoumarin alleviate inflammatory response by inhibiting the release of a variety of proinflammatory factors (e.g., activin A, ciliary neurotrophic factor, and fractalkine) in FLS of RA models (Bi et al, ; Chen et al, ; Deng et al, ; Huang et al, ; Jia et al, ; Li et al, ; Liang et al, ; Lin, Sato, & Ito, ; Liu, Feng, et al, ; Mao, Sun, Pei, & Zhang, ; Su et al, ; Su et al, ; Sun et al, ; Sun et al, ; Sun & Li, ; Sung et al, ; Tang et al, ; Tian, Chen, Gao, Li, & Xie, ; Venkatesha, Astry, Nanjundaiah, Yu, & Moudgil, ; Wang, Sun, & Jin, ; Wei et al, ; Yang et al, ; Yang et al, ; Zhang et al, ; Zheng et al, ; Zuo et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…In addition to inflammatory damage, FLS also plays an essential role in cartilage destruction (Pan et al, ). Therefore, the decrease in FLS activity by some components is also beneficial to the protection of cartilage in RA models, including triptolide, celastrol, geniposide, paeoniflorin, clematichinenoside AR, kirenol, tanshinone IIA, bauchampine A, betulinic acid, baicalein, 1,7‐dihydroxyl‐3,4‐dimethoxylxanthone, catechin, kaempferol, licochalcone A, luteolin, quercetin, ramosissimin, α‐mangostin, berberine, fissistigmine A, matrine, norisoboldine, oxymatrine, piperlongumine, sinomenine, tamaractam, caffeic acid, chlorogenic acid, paeonol, daphnetin, and leonurine (Bi et al, ; Chen et al, ; Chen et al, ; Deng et al, ; Hong et al, ; Hua et al, ; Jie et al, ; Kusunoki et al, ; Li et al, ; Li et al, ; Li et al, ; Liang et al, ; Liu et al, ; Liu, Feng, et al, ; Lou et al, ; Lou et al, ; Luo et al, ; Pan et al, ; Pan et al, ; Shu et al, ; Su et al, ; Su et al, ; Sun et al, ; Sun et al, ; Sun et al, ; Sung et al, ; Tang et al, ; Wang et al, ; Wang, Dai, et al, ; Wang, Sun, & Jin, ; Xu et al, ; Yang, Dong, & Li, ; Yao et al, ; Yi et al, ; Zhang et al, ; Zhang, Chen, et al, ; Zheng et al, ; Zhou et al, ; Zuo et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%